The influence of the tamped out foundation on the calculable strength of the footing base/Plūktinio pamato formos įtaka pado pagrindo skaičiuojamajam stiprumui - Alikonis, Antanas (Journal of Civil Engineering and Management, 2001)
Foundations, erected in the tamped out trenches, are distinguished for a greater bearing capacity of the base in comparison with the foundations which are erected in the dug out trenches. They are also economic in respect of energy and material. The building practice shows that tamped out, that is erected in tamped out trenches, foundations can be successfully used in many types of soil. The tamped out foundation of the truncated pyramid form can bear the bigger part of the loading by its sides because of the leaning sides of the foundation and the foundation of the cylindrical form can bear for smaller part of the loading because its sides are perpendicular. The bearing capacity of the sides of the tamped out foundation is calculated using theoretical formulas which are rather complicated and it requires figure meaning of Geotechnical features of soil. The author investigated theoretically the distribution of the effecting strength between the bottom and the tamped out foundation. The strength whitch falls on the bottom of the foundation was used to define the calculable strength of the bottom of the foundation. According to the strength that falls on the bottom of the foundation the tension calculated when n=1,2,3% which in considered the calculable strength of the bottom of the foundation. The calculable strength of the bottom of the base of the foundation is connected with the conic strength of natural soil qc, which is got by statical serenading. The experiments were carried out in sand soils the conic strength of which was 4–6MPa. According to the results of the experimental research the formula was deduced to define the calculable strength of the bottom of the tamped out foundation of the truncated pyramid shape. The experiments were carried out trying static loading on 6 experimental foundations in sand soils the conic strength of which was 4–8MPa. During the experiment the calculable strength of the bottom of the tamped out foundation of the cylindrical form was investigated. Analyzing the results of these experiments the strength which falls on the bottom of the foundation was distinguished. The tension on the plane of the bottom of the foundation was defined according to the settlings of the foundation form loading. The settlings of the foundation in this situation was 1, 2, 3% of the foundation diameter. These tensions are considered the calculable strength of the base of the bottom of the foundation. According to the results of the experimental research the formula was deduced to define the calculable strength of the bottom of the tamped out foundation of the cylindrical form. This calculable strength was defined according to the natural sand soil conic strength and accepted ratio of settling and the diameter of the foundation. The results of the reseach show that the calculable strength of the bottom of the tamped out foundation of the cylindrical form which is erected in sand soils is much bigger that the calculable strength of the tamped out foundation of the truncated pyramid shape. The figure meaning of the calculable strength of the bottom of the base of the tamped out foundation depends on the form of the foundation, on the conic strength of the soil, which is got by statical sounding of natural soil and it depends on the accepted percentage ratio of the settling and the diameter of the foundation. Article in Lithuanian. First Published Online: 30 Jul 2012